Study of AlGaN/GaN Vertical Superjunction HEMT for Improvement of Breakdown Voltage and Specific On-Resistance - Miao Zhang (IEEE, 2021)
A GaN-based vertical superjunction high electron mobility transistor (SJ HEMT) with a composite structure (CS-SJ HEMT) is proposed and analyzed by Silvaco TCAD to improve the breakdown voltage and specific on-resistance (RonA). In this paper, CS-SJ HEMT is compared with SJ HEMT with traditional structure (TS-SJ HEMT), SJ HEMT with only particular doping pillars (DP-SJ HEMT) and SJ HEMT with only special P-gate (SP-SJ HEMT). The particular doping pillars mean the doping concentration of n-pillar increases with a gradient from top to bottom, and the concentration of p-pillar is the same as the middle of n-pillar, which reduces the RonA by only 4%. The special P-GaN cap layer can reduce the RonA by 10%, and it can even increase the on-state current in the saturation region. The CS-SJ HEMT combines both doping pillars and special P-gate structures, and the RonA can be reduced by 14%. By the optimized design, the RonA can be reduced by 30% with BV = 2580 V, or the RonA can be reduced by 21% with BV = 2720 V. These results show that the composite structure of SJ HEMT contributes to improving the BV and RonA and propose a useful approach for improving the vertical HEMTs.